University Students’ Decision-Making Model in Consuming Alternative-Protein Meatballs: A Gender Perspective - Anggraeni, Anindita Putri Puspita; Setiawan, Budi; Hartono, Rachman (Universitas Panji Sakti, 2025)
Healthy and sustainable diets play a crucial role in addressing global challenges, including climate change, food security, and public health. This study focuses on plant-based meatballs, analyzing their appeal as an environmentally friendly, resource-efficient, and healthy alternative protein source. Conducted among undergraduate students at Brawijaya University, the study examines the impact of innovation adoption characteristics on consumption intentions, with environmental concerns serving as a moderating factor. Utilizing an online survey distributed to 385 respondents, data were collected over two weeks in October 2024. Results reveal that plant-based meatballs received the highest average scores in compatibility (Attractiveness: 3.94, Safety: 3.81) and relative advantages (Environmentally Friendly: 3.84, Food Security: 3.28), as well as in consumption intention for Health Interest (3.88). Statistical analyses confirmed strong convergent validity, reliability, and predictive performance, with meatballs showing significant influence on consumption intention (f² = 0.839). This research highlights the strategic role of students as agents of change in promoting sustainable diets, providing actionable insights for developing marketing strategies and policies to support the adoption of plant-based alternatives. Emphasizing the environmental and health benefits of plant-based meatballs could drive their wider adoption and contribute to a more sustainable food system in Indonesia.